Acute exercise following skill practice promotes motor memory consolidation in Parkinson's disease - Wanner, Philipp; Winterholler, Martin; Gaßner, Heiko; Winkler, Jürgen; Klucken, Jochen; Pfeifer, Klaus; Steib, Simon (Neurobiology of Learning and Memory, 2021)
Acute cardiovascular exercise has shown to promote neuroplastic processes supporting the consolidation of newly acquired motor skills in healthy adults. First results suggest that this concept may be transferred to populations with motor and cognitive dysfunctions. In this context, Parkinson's disease (PD) is highly relevant since patients demonstrate deficits in motor learning. Hence, in the present study we sought to explore the effect of a single post-practice exercise bout on motor memory consolidation in PD. For this purpose, 17 patients with PD (Hoehn and Yahr: 1 – 2.5, age: 60.1 ± 7.9 y) practiced a whole-body skill followed by either (i) a moderate-intense bout of cycling, or (ii) seated rest for a total of 30 min. The motor skill required the participants to balance on a tiltable platform (stabilometer) for 30 s. During skill practice, participants performed 15 trials followed by a retention test 1 day and 7 days later. We calculated time in balance (platform within ± 5° from horizontal) for each trial and within- and between-group differences in memory consolidation (i.e. offline learning = skill change from last acquisition block to retention tests) were analyzed. Groups revealed similar improvements during skill practice (F4,60 = 0.316, p = 0.866), but showed differences in offline learning, which were only evident after 7 days (F1,14 = 5.602, p = 0.033). Our results suggest that a single post-practice exercise bout is effective in enhancing long-term motor memory consolidation in a population with motor learning impairments. This may point at unique promoting effects of exercise on dopamine neurotransmission involved in memory formation. Future studies should investigate the potential role of exercise-induced effects on the dopaminergic system.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Cardiovascular exercise; Motor learning; Neuroplasticity; Neurorehabilitation; Offline learning; Parkinsonism